A Multicenter Retrospective Study Comparing Surgical Outcomes Between the Overlap Method and Functional Method for Esophagojejunostomy in Laparoscopic Total Gastrectomy: Analysis Using Propensity Score Matching. Issue 1 (February 2022) - Ebihara, Yuma; Kurashima, Yo; Tanaka, Kimitaka; Nakanishi, Yoshitsugu; Asano, Toshimichi; Noji, Takehiro; Nakamura, Toru; Murakami, Soichi; Tsuchikawa, Takahiro; Okamura, Keisuke; Murakami, Yoshihiro; Murakawa, Katsuhiko; et al.
Abstract : Background: This study aimed to compare the postoperative outcomes after laparoscopic total gastrectomy (LTG) with esophagojejunostomy (EJS) performed using the overlap method or the functional method in a multicenter retrospective study with propensity score matching. Methods: We retrospectively enrolled all patients who underwent curative LTG for gastric cancer at 6 institutions between January 2004 and December 2018. Patients were categorized into the overlap group (OG) or functional group (FG) based on the type of anastomosis used in EJS. Patients in the groups were matched using the following propensity score covariates: age, sex, body mass index, American Society of Anesthesiologists physical status, extent of lymph node dissection, and Japanese Classification of Gastric Carcinoma stage. The surgical results and postoperative outcomes were compared. Results: We identified 69 propensity score-matched pairs among 440 patients who underwent LTG. There was no significant between-group difference in the median operative time, intraoperative blood, or number of lymph nodes resected. In terms of postoperative outcomes, the rates of all complications [Clavien-Dindo (CD) classification ≥II; OG 13.0 vs. FG 24.6%, respectively; P =0.082], complications more severe than CD grade III (OG 8.7 vs. FG 18.8%, respectively; P =0.084), and the occurrence of EJS leakage and stenosis more severe than CD grade III (OG 7.3% vs. FG 2.9%, P =0.245; OG 1.5 vs. FG 8.7%, P =0.115, respectively) were comparable. The median follow-up period was 830 days (range, 18 to 3376 d), and there were no differences in overall survival between the 2 groups. Conclusions: There was no difference in surgical outcomes and overall survival based on the type of anastomosis used for EJS after LTG. Therefore, selection of anastomosis in EJS should be based on each surgeon's preference and experience.